The Future of East Asia (Asia Today, 2018)
This book collects some of the most influential scholars in international relations who focus on Asia globally in exploring the challenges of diplomacy faced in Asia as US policy drastically changes. The president-elect has suggested policies which, if implemented, would radically transform the way that the region functions; what will this mean in practice? China's government is also retrenching nationalist positions; what is the future of China, and what does that mean for the region? A wide range of distinguished scholars, concerned about the future, have contributed their thoughts in an attempt to spark a global dialogue. .